Pengaruh Daya Tarik Wisata dan Fasilitas layanan Terhadap Kepuasan Wisatawan Di Wisata Pamah View, Kabupaten Langkat - Supriadi Siagian; Mita, Merry Moy (TOBA: Journal of Tourism, Hospitality, and Destination, 2022)
This study aims to determine the effect of tourist attraction and service facilities on tourist satisfaction in Pamah View tourism, Langkat district. The population in this study were all people who came to travel to Pamah View, Langkat district. In this study, data were collected through a questionnaire method for 95 respondents who were obtained using random sampling technique. The type of data in this study is quantitative data analysis, quantitative analysis includes validity and reliability tests, classical assumption test, hypothesis testing through F test and t test and analysis of the coefficient of determination (R2). The data analysis technique used is multiple linear regression analysis using the SPSS Version 21 application. The results show that Attractiveness (X1) and Service Facilities (X2) simultaneously significantly influence tourist satisfaction in Pamah View tourism, Langkat district. Therefore, it is necessary to renew the form of tourism so that it has an attraction for tourists and also improves service facilities must be packaged and run properly in increasing tourist satisfaction in Pamah View tourism, Langkat district.